2021
DOI: 10.1155/2021/9565379
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Resource Carbon Emission Allocation Efficiency Based on Blockchain Consensus Algorithm

Abstract: This paper takes the secondary low-carbon supply chain composed of a manufacturer and a retailer as the research object and takes the government subsidy strategy of low-carbon supply chain as the research theme, the government invests in the construction of blockchain technology application platform, and supply chain enterprises use blockchain technology for compensation. Under this background, considering consumers’ low-carbon preference and green trust, a three-stage game model dominated by the government an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Because its own system distributed technology architecture is very complex, all nodes need to synchronize information, which easily wastes power resources. Second, in terms of application, the necessary prerequisite for the application of blockchain is the establishment of a complete public infrastructure in the whole or at least part of the important scenarios of energy saving and carbon reduction [155,156], which often implies enormous construction costs in the early stage. Overall, the current problems faced are the lack of coordinated innovation management, multi-stakeholder innovation, and the construction of public infrastructure [157,158].…”
Section: Economic Benefitsmentioning
confidence: 99%
“…Because its own system distributed technology architecture is very complex, all nodes need to synchronize information, which easily wastes power resources. Second, in terms of application, the necessary prerequisite for the application of blockchain is the establishment of a complete public infrastructure in the whole or at least part of the important scenarios of energy saving and carbon reduction [155,156], which often implies enormous construction costs in the early stage. Overall, the current problems faced are the lack of coordinated innovation management, multi-stakeholder innovation, and the construction of public infrastructure [157,158].…”
Section: Economic Benefitsmentioning
confidence: 99%
“…[5] found that green supply chain management practice had positive effects on operational performance and technological innovation. Yin [6] studied a secondary low-carbon supply chain composed of manufacturers and retailers. Wei et al [7] highlighted the vital function that green supply chain management in the circular economy.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%